Analisis Dan Perancangan Program Inventori Pada Lucky Com - Sama, Hendi; Siahaan, Mangapul; Syahputra, Bayu; Sabariman; Adi (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2025)
Lucky Com is a company where this company is engaged in the distribution of mobile phone accessories such as earphones, power banks, chargers, cables and so on. There are many types of goods available at Lucky Com so that there is a problem in recording stock which is done manually an error occurs. The author would like to provide input with the hope that it can be useful to overcome this problem by creating a web-based inventory system that can facilitate recording stock and goods transactions. The web-based inventory system can be processed by utilizing the PHP programming language and using hosting as a storage space that can be accessed online so that the system can be accessed online as well, and the author also uses a domain as the website address that will be created